The Displacement Effect of Reemployment Bonus Programs - Davidson, Carl; Woodbury, Stephen A. (Journal of Labor Economics, 1993)
We develop a partial equilibrium matching model of the labor market in order to examine whether adoption of a reemployment bonus would displace workers not offered the bonus. We examine the displacement effect for (a) unemployment insurance (UI)-eligible workers who are offered but do not find a job in time to qualify for a bonus and (b) UI-ineligible workers who are never offered a bonus. The model predicts minimal displacement of the former group. But for the latter group, the model predicts an increase in unemployment duration of .2-.4 week and an increase in unemployment of up to 2 per thousand.